KANDUNGAN LOGAM BERAT Pb DAN Cd PADA SEDIMEN DAN KERANG DI PERAIRAN BATAM - S, Ismarti; Amelia, Fitrah; Ramses, Ramses (Universitas Riau Kepulauan, 2015)
The determination of metal content of lead (Pb) and cadmium (Cd) on sediments and shellfish samples from coastal waters’s of Batam. Samples was collected from 6 location grably. Sediments and shellfish samples obtained dried in an oven at a temperature of 80-105oC. The samples were dried crushed and made wet digestion with nitric acid. Pb and Cd levels were determined using spectrophotometry method at 228.72 nm resonance line Cd and Pb to 283.30 nm. The results showed that the levels of heavy metals Pb and Cd in sediments and shellfish samples varied. The highest levels of Pb and Cd found in sediments from Buluh Island, respectively 20.12 mg / kg for Pb and 0,24mg / kg for cadmium. Based on the value SQG, concentrations of Pb and Cd metal in sediments is still at the standards for sediments that have not been contaminated. Pb levels in the shells found at all sampling locations exceeded the specified threshold BPOM RI, whereas Cd metal levels are still below the threshold set BPOM RI, except in shellfish samples from Buluh Island.